The Effort to Prevent Traffic Congestion Through The Semarang Police's Turjagwali - SARAH YUDEA L.TORUAN TORUAN (Police Studies Review, 2022)
Traffic congestion is one of the problems in the field of traffic that still cannot be resolved in Indonesia. This study describes how traffic jams occur at the Semarang Police Station where the biggest congestion is at Simpang Bawen. The purpose of this study is how to describe the regulation, guard, escort, traffic patrol in preventing traffic jams at the Semarang Police Station. The Semarang Police Satlantas made efforts through turjagwali then traffic jams could be overcome. Turjagwali is an operational activity that is preventive in nature in preventing traffic jams. To discuss this research, the author uses George R Terry's Management theory, Albert Humley's SWOT Analysis theory, and the concept of Turjagwali’s Traffi. The approach used in this study is a qualitative approach. Data was collected by using interview, observation, and document review techniques. Meanwhile, data analysis was carried out by reducing data, presenting data, and drawing conclusions. The results show that the efforts that have been made by traffic police through turjagwali activities still need to be maximized, especially in human resources, administration, and implementation methods. This is influenced by internal and external factors. Internally, the mental discipline of members, the use of technology, the routine implementation of anev as supporting factors. Meanwhile, the guidelines for implementing the tasks are not yet complete and the quantity is not sufficient to become an inhibiting factor. Meanwhile, externally there is coordination with outside agencies and volunteers from the community as supporters, while the low awareness of the community for orderly traffic is an inhibiting factor. Based on the results of the study, the authors suggest to carry out cross-functional and sectoral coordination as well as the existence of both internal and external traffic functions. Also, the author suggests implementing a contra flow system, a one-way system, and an odd-even system.